PERKEMBANGAN PENDIDIKAN MATEMATIKA TINGKAT SD DI INDONESIA, MALAYSIA, DAN JEPANG - Ifada Novikasari (Universitas Khairun, 2013)
Improving the quality of teaching and learning of primary mathematics has always been a major concern of mathematics educators. TIMSS is a collaborative research project sponsored by the International Association for the Evaluatioan of Educational Achievement (IEA). It is the largest and most ambitious study of comparative educational achievement tests in mathematics and science ever undertaken. Every effort was made to help ensure that the tests represented the curricula of the participating countries and that the items did not exhibit any bias towards or against particular countries, including modifying specifications of the items by subject matter specialists within the participating countries, and conducting thorough statistical item analysis of data collected in the pilot testing. This article briefly summarizes develompment of Indonesian, Malaysian and Japanese mathematics education. It concludes with description of a method for teaching mathematics in those countries.